Native plants and neuroprotective effects in diabetes mellitus - Rey, Mariana (2019)
In Cuyo region (Argentine) Tessaria absinthioides (Ta) and Oxalis erythrorhiza (Oe) are popularly consumed to regulate glucose (Glu) and cholesterol (Chol) levels, lacking of scientific support. Several works indicate that 85% of world population uses "medicinal plants" to treat its health. Diabetes mellitus courses chronic hyperglycemia, oxidative stress state and neurodegenerative changes. Previously we had shown effects of Ta and Oe decoctions on LXRs expression in hypothalamus. In this work, adult male rats (SD), controls (C,i.p.veh) or diabetics (D,i.p.STZ30mg/Kg) drunk 10%W/V decoctions of Ta (CTa/DTa), Oe (COe/DOe) or water (CW/DW) by 4 weeks. Glu, Chol and triglycerides (Tg) levels were measured on blood samples by commercial kits. The hypothalamic neural NOS (nNOS) and Neurofilaments200 (NF200, 3 different bands) expression levels were studied by WB. Compared to CW, DW, DOe and DTa had higher levels of Glu (350%, 200% and 200%; p<0.05) and Tg (200%, 300% and 200%; p<0.05). But, Glu in DTa and DOe was lower than DW (both 150%; p<0.05). No changes were observed in Chol among groups. All NF200 bands were higher in DW, COe and CTa than CW (28%; 14% and 19%; p<0.05). However, the value of NF200 in DTa were lower than DW (25%; p<0.05) and closer to CW. The nNOs in DW and COe were higher than in CW (43% and 70%; p<0.05), however the decoctions had not effect on D. Results suggest that these plants could have metabolic and neuroprotective effects. A more extended treatment will be necessary to propose Oe and Ta like new therapeutic tools